Blankaartia sinnamaryi (Trombidiformes: Trombiculidae) parasitizing birds in Southeastern Brazil, with notes on rickettsia detection - Bassini-Silva, Ricardo; Jacinavicius, Fernando de Castro; Maturano, Ralph; Muñoz-Leal, Sebastián; Ochoa, Ronald; Bauchan, Gary; Labruna, Marcelo Bahia; Barros-Battesti, Darci Moraes [UNESP] (FapUNIFESP (SciELO), 2018)
The larvae of the family Trombiculidae are ectoparasites of vertebrates, including birds. The bite of some species can cause deep lesions and severe skin reactions in the host, these can lead to dermatitis, popularly known as trombiculiasis. A morphological study of chiggers collected on birds from the state of Minas Gerais in Southeastern Brazil discovered Blankaartia sinnamaryi-infestation on Passeriformes birds. Molecular studies of the disclosed the 18S rDNA sequences of the mite, and the detection of a Rickettsia sp. in this chigger mite species.
Blankaartia sinnamaryi (Trombidiformes: Trombiculidae) parasitando aves no sudeste do Brasil, e notas sobre a detecção de Rickettsia
Keywords: Chiggers; Dermatitis; Passeriformes; Rickettsia